ҚАЛЫПТЫ ЖƏНЕ ПАТОЛОГИЯ ЖАҒДАЙЫНДАҒЫ ЖАНУАРЛАР АҒЗАСЫНЫҢ ФУНКЦИОНАЛДЫ КҮЙІН КИРЛИАН ЭФФЕКТІСІ БОЙЫНША ЗЕРТТЕУ (Experimental biology, 2015)
In the paper, the new experimental materials are showed on the basis of resulting the functional features of animals’ organisms in norm and at cancer diseases by means of Kirlian effect.
Keywords: Kirlian effect